IFC and HBL Supporting Job Creation in Pakistan - International Finance Corporation (World Bank, Washington, DC, 2017)
IFC, a member of the World Bank Group, contributes to the World Bank mission of global poverty reduction by creating opportunities for people to improve their lives through private sector solutions. In Pakistan, IFC’s strategy has focused on addressing the key challenges that affect private sector development, from investing in the infrastructure sector, including energy, to enhancing access to finance, with a view to improving the conditions for growth and employment generation. As part of its country program, IFC has focused on increasing access to finance for small and medium enterprises (SMEs), which are the backbone of Pakistan’s economy as they constitute more than 90 percent of total private enterprises in the formal industrial sectors and employ over 70 percent of the labor force. Often these SMEs struggle to obtain the financing needed to grow and create jobs. For this reason, IFC has partnered with financial institutions to improve service provision to SMEs and stimulate economic development across the country. Since 2007, IFC has been engaged with HBL, Pakistan’s largest private sector commercial bank, and provided financing to strengthen the bank’s capital following its privatization, as well as advised on how to scale up the bank’s SMEs portfolio in a sustainable manner. The objective of this study is to develop an understanding of the relationship between access to finance for small and medium enterprises (SMEs) and job creation. IFC has analyzed a sample of more than 100 SMEs that obtained loans from its client, Habib Bank Ltd (HBL), in 2009 in Pakistan, at a challenging time for the country.